Rancang Bangun Prototipe Sistem Pendeteksi Pencurian Burung Berbasis IOT - Hudi, Siti Azka Rahmawati; Rafid Rziqullah; Maria Agustin, S.Kom., M.Kom. (MULTINETICS, 2022)
The crime of bird theft has always existed in the community and can occur at any time. It is the duty of bird owners to improve the security of their cages so that birds are always protected. Online news media also often report cases of bird theft as in the news from antvklik.com on January 3, 2018, there was a bird theft. The perpetrators acted by forcibly opening the cage door. The action was caught on CCTV, but the perpetrator was not caught. Based on this incident, CCTV can only act as a scout or record the situation, therefore a solution was made by designing a bird theft detection system using a human detector sensor to detect human presence which is connected to the ESP32 camera module to take pictures of the situation outside the cage when suspicious human presence detected. The information is sent to the owner via the Telegram Bot. The research method used is the prototyping method. In addition, it is connected with plus RFID Card technology to open the drum door. The result of this research is that each component in this system has functioned according to the algorithm and has been integrated according to the design that has been made.